Financial Crisis and Credit Crunch in Korea : Evidence From Firm-Level Data - Lee, Jong-Wha (IMF Working Papers; Working Paper ;, 2000)
This paper analyzes the credit crunch following the recent financial crisis in Korea. Using enterprise-level data, we find that there were big differences in the magnitude of the credit contraction across different types of firms. In particular, chaebol (conglomerate)-affiliated firms appeared to have lost the preferential access to credit they enjoyed in the pre-crisis period, and credit appears to have been reallocated in favor of more efficient firms. This suggests that the credit crunch suffered by certain sectors can be attributed to the adjustment by banks and enterprises to the restructuring of the financial sector, rather than to tight monetary policy or an external credit constraint.